Public-private partnerships for innovation-led growth in agrichains: a useful tool for development in Latin America? - Hartwich, Frank; González, Carolina; Vieira, Luis-Fernando (International Food Policy Research Institute, 2005)
Public-private partnerships have become increasingly important as an arrangement that serves to encourage innovation in agricultural production chains in Latin America. However, some observers have expressed concern that this institutional arrangement may mostly favor the interests of the private sector without producing sufficient social benefits for the public. This paper presents the results of a study of 124 cases of public-private partnerships in agricultural innovation in nine countries in Latin America. The data from the study suggest that the partnership concept is used to generate agricultural innovations in many different ways, involving public research and private entities to varying degrees and focusing on different types of agricultural products, processing, or marketing. The results indicate that public as well as private sector actors often enter into partnerships based on unclear expectations of the benefits to be obtained, but once involved, these actors are usually satisfied with the results. Given the high degree of satisfaction that partners experience in public-private partnerships, they constitute an interesting new tool for development. However, in many cases public sector agents do not clearly establish public priorities; in consequence, public sector goals are not addressed sufficiently. Also due to the limited commitment of some of the partners to partnerships their potentials of generating synergy are not met. One key recommendation to emerge from the study is that when entering into public-private partnerships, public agents should ensure that these partnerships comply with public needs.